2017
DOI: 10.1080/00905992.2017.1312324
|View full text |Cite
|
Sign up to set email alerts
|

Unattainable past, unsatisfying present – Yugonostalgia: an omen of a better future?

Abstract: Nostalgia for the Socialist Federal Republic of Yugoslavia,yugonostalgia, has become widespread throughout the former Yugoslavia. It takes various forms and expressions, but it represents a selective and largely embellished remembrance, influenced by the need of those who engage in it to escape from the unsatisfying present they live in. In most cases, yugonostalgia is a bittersweet craving for the past – passive, static, and restricted. The paper argues that the actions inspired by yugonostalgia not only can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…Hovewer, my evaluation that the framework of Yugo-nostalgia is not appropriate for this case stands independently from the motivations some participants may have for rejecting it. 6 The research on other former Yugoslav republics indicates the existence of a similar division between positive social frames available from individual narratives (see, for example, Maksimović, 2017) and negative reevaluations of Yugoslavia dominating public discourse (see, for example, dominant presentations of socialist Yugoslavia in Slovenian newspapers in Pušnik, 2017).…”
Section: Endnotesmentioning
confidence: 96%
See 1 more Smart Citation
“…Hovewer, my evaluation that the framework of Yugo-nostalgia is not appropriate for this case stands independently from the motivations some participants may have for rejecting it. 6 The research on other former Yugoslav republics indicates the existence of a similar division between positive social frames available from individual narratives (see, for example, Maksimović, 2017) and negative reevaluations of Yugoslavia dominating public discourse (see, for example, dominant presentations of socialist Yugoslavia in Slovenian newspapers in Pušnik, 2017).…”
Section: Endnotesmentioning
confidence: 96%
“…The use of the past to address the present concerns was likewise noted in the recent research on Yugo-nostalgia. Several studies have found that individuals from different former Yugoslav republics, of various ages and educational and class backgrounds, use the positive images of Yugoslavia as a point of comparison with the unsatisfactory living conditions in their different post-Yugoslav societies (Maksimović, 2016, 2017; Palmberger, 2016; Spasić, 2012; Velikonja, 2008, 2009; Volcic, 2007). These authors noted how, despite the negative re-evaluation and the rejection of Yugoslavia among the nationalistic elites and in the official discourse of these societies, their ‘ordinary citizens’ use their own memories of Yugoslavia and, in case of the youth, those of the older generations to criticize the current economic, political and moral conditions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Memory and collective memory studies have taken a significant interest in the countries of the former state of Yugoslavia, mostly because of the long history of conflict in the Balkans and the active role that this history plays in contemporary politics in the region (Karge, 2009;Ramet, 2013;Putnik, 2016;Akrivoulis, 2017;Maksimović, 2017). The following section of this paper sets out this regional context, within which the contemporary role of events in collective memory will then be examined.…”
Section: Collective Memorymentioning
confidence: 99%
“…jugonostalgię, to są one odnośnikami w narracjach moich rozmówców i pokazują różnice między warunkami, w jakich dorastali młodzi Macedończycy w Tetowie i ich rodzice. Jugonostalgia, jak przekonuje Maja Maksimović, jest zbiorem wyselekcjonowanych wspomnień o czasach świetności Jugosławii (Maksimović 2017(Maksimović : 1068, dlatego nie przywołuje prawdziwego wspomnienia tego, jak wyglądało życie w czasach Jugosławii, ale jego wyidealizowany obraz. Warto zaznaczyć, że wspomnienia Jugosławii moich respondentów nie mają podstawy biograficznej, lecz są zapożyczone z historii rodziców i wytworów popkultury, takich jak filmy i muzyka, co w literaturze naukowej nazywa się pamięcią protetyczną (Landsberg 2004: 20).…”
Section: Doświadczenie Zbyt Szybkiego Regresuunclassified
“…W przypadku mieszkańców Tetowa jest to ekonomiczny dobrobyt, solidarność poza podziałami etnicznymi, bezpieczeństwo oraz bogate życie kulturalne i społeczne. Jugonostalgia jest ważnym elementem, pomocnym w zrozumieniu rozczarowania wśród dorastających Macedończyków, ponieważ jest ona zorientowana w kierunku fantazji dotyczących przeszłości (Maksimović 2017(Maksimović : 1068, czyli wszystkich tych możliwości dostępnych dla ich rodziców, a dla nich już nieosiągalnych.…”
Section: Doświadczenie Zbyt Szybkiego Regresuunclassified